Strategy in the digital age : mastering digital transformation - Lenox, Michael (Tantor Media, Inc., 2023)
Digital transformation is much more than building a digital infrastructure to gather and process data. It is about understanding how digital technologies enable the creation of innovative services and products. It is about identifying new competitive positions and business models and thinking critically about how to both create and capture value. Strategy in the Digital Age directly engages these concerns and provides a comprehensive roadmap for planning a successful digital strategy and executing a digital transformation in organizations. Covering major topics such as big tech, data analytics, artificial intelligence, blockchain, cryptocurrency, autonomy, cybersecurity, data privacy, and antitrust, strategy expert Michael Lenox outlines a set of novel, original frameworks to help those undertaking digital transformation at their organization devise their strategy. Listeners will also come away with a greater understanding of how to navigate the human dimension of digital transformation and tackle the numerous social and policy challenges raised by digital technology. With insights from major companies such as Spotify, Facebook, and Uber, Lenox delivers a compelling volume that offers both a foundational understanding of this dynamic environment and an action plan for those seeking a path to digital strategy implementation for their organization.